BMP10 accelerated spinal astrocytic activation in neuropathic pain via ALK2/smad1/5/8 signaling - Bian, Jiang; Luo, Min; Tian, Yunyun; Zhang, Xuejuan; Zhang, Bangjian; Yin, Li; Zhang, Yuehui (Frontiers in Pharmacology, 2024)
Astrocytic activation in the spinal dorsal horn contributes to the central sensitization of neuropathic pain. Bone morphogenetic protein (BMP) 10, one of the BMPs highly expressed in the central nervous system, has been demonstrated to have an accelerated effect on astrocytic activation. In this study, BMP10 levels were increased in the L4-6 ipsilateral spinal dorsal horn of spared nerve injury (SNI) mice and particularly elevated in astrocytes. Consistently, glial fibrillary acidic protein (GFAP) and phosphorylated Smad1/5/8 were upregulated in the L4-6 ipsilateral spinal dorsal horn after SNI, indicating the activation of astrocytes and Smad1/5/8 signaling. An intrathecal injection of BMP10 siRNA abrogated pain hypersensitivity and astrocytic activation in SNI mice. In addition, intrathecal administration of BMP10 peptide evoked pain hypersensitivity and astrocytic activation in normal mice, and this action was reversed by inhibiting the activin receptor-like receptor 2 (ALK2). Furthermore, targeting Smad1 in vitro with the help of siRNA inhibited the activation of astrocytes induced by lipopolysaccharides (LPS). Finally, targeting Smad1 abrogated BMP10induced hypersensitivity and activation of astrocytes. These findings indicate that the BMP10/ALK2/Smad1/5/8 axis plays a key role in pain hypersensitivity after peripheral nerve injury, which indicates its stimulative ability toward astrocytes.